Mothers and Sons: The Importance of Feminist Maternal Practice and the Potential for Doing Gender with Boys - Epstein, Sarah (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
This article reviews the importance of feminist maternal practice for providing the theoretical potential for maternal agency and considers what this may mean when integrated with the idea that gender is relationally produced. The experiences of Australian feminist mothers raising boys are used to highlight the importance of the maternal subject as agentic and capable of repositioning both her own and her sons’ gendered subjectivities. Although the ideas put forward are authoritative only from and within the specified locale of urban living—predominantly white, able-bodied, cisgender, and heterosexual Australian women—this does not mean the knowledge is ahistorical and noncontextual. Rather, this means women’s lived experiences are affected by and continuously enact and interact with (among other things) wider social narratives about gender and about mothers and sons. This article argues that feminist maternal practice reinvigorates the potential for the maternal subject to enact change in gender relations from within the mother and son relationship.